TEKS GEGURITAN MALELEMESAN DALAM PUPULAN RARIPTAN KASAWUR KARYA KI JAKAWANA ANALISIS BENTUK DAN AMANAT - Angraeni, Diyan (Humanis, 2015)
Research on Geguritan Malelemesan text is about the analysis of the shape and mandate. This analysis aims to describe the shape and describe the mandate contained in the text Geguritan Malelemesan. Research Geguritan Malelemesan textusing structural theory based on the theory of Wellek and Werren, Ratna, Luxemburg, Taum. The methods and techniques used are divided into three stages, namely (1) phase by using the method of providing data refer aided by using the technique of recording and translation techniques, (2) phases using qualitative methods of data analysis assisted with descriptive analytic techniques, and (3) phase presenting the results of data analysis using formal methods, assisted by informal deductive techniques and inductive techniques. Dissclosure Geguritan Malelemesan text structure on the shape of the structure includes a code language and literature, language diversity, and style as well as structure that includes the contents of the beginning and the end. Mandate contained in the text Geguritan Malelemesan include love between men and women that love each other and respect, love of parents to children so that parents are wise in making a decision and was willing to do anything for the happiness of their children, children to parents so that a filial son parents should not forget as a child are indebted to the parents, one must speak good words and gentle to the parents as well as with others.
Keywords: geguritan, shape, mandate